Human Factors Constructs as Antecedents of Continuance Intention Toward Public Electric Vehicle Charging Stations: An Extended Theory of Planned Behavior - Ma. Janice J. Gumasing (World Electric Vehicle Journal, 2026)
The rapid expansion of electric vehicle (EV) charging infrastructure has increased the importance of improving the user experience alongside expanding charging availability. While previous studies have primarily examined EV adoption from technological, economic, and infrastructural perspectives, limited research has investigated how Human Factors characteristics of charging systems influence users’ continuance intention. This study extends the Theory of Planned Behavior (TPB) by integrating Human Factors constructs as antecedents of behavioral beliefs associated with continuance intention toward public EV charging stations in the Philippines. A quantitative cross-sectional survey was conducted among 286 EV users in the National Capital Region, and the proposed model was evaluated using Partial Least Squares Structural Equation Modeling (PLS-SEM). Interface usability significantly influenced both attitude and perceived behavioral control, while participatory ergonomics significantly influenced subjective norm. Physical ergonomics, cognitive ergonomics, and accessibility did not significantly predict their proposed behavioral beliefs. Among the TPB constructs, perceived behavioral control and attitude significantly predicted continuance intention, whereas subjective norm was not significant. Furthermore, interface usability exhibited significant indirect effects on continuance intention through both perceived behavioral control and attitude. The findings demonstrate that Human Factors characteristics contribute selectively to the behavioral mechanisms underlying continued charging-station use, with perceived behavioral control emerging as an important pathway linking the charging experience with continuance intention. The study extends TPB by positioning Human Factors as antecedents of behavioral beliefs in a post-adoption context and highlights the importance of usable, understandable, and manageable charging interactions in supporting continued engagement with public EV charging infrastructure.